Analisis Pendapatan dan Kelayakan Usaha Kopra di Desa Tulabolo Barat Kecamatan Suwawa Timur Kabupaten Bone Bolango - Merlin Moha; Amir Halid; St. Aisyah R (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Most farmers in West Tulabolo Village, located in East Suwawa District, carry out extensive coconut cultivation. Farmers obtain coconut in granular form. Usually, coconut farmers who live in West Tulabolo Village sell copra as the primary means of commercialising their coconut products. The main objective of this research is to determine the income and feasibility of the copra industry in West Tulabolo Village, located in East Suwawa District, Bone Bolango Regency. The research location was deliberately chosen because the potential for coconut cultivation is quite significant. The research was carried out from March to June 2023. The population in this study consisted of a sample of 15 farmers selected using a saturated sampling technique, which included the entire copra farming community. This research uses primary and secondary data sources. This research uses a quantitative descriptive methodology to analyse the data. Research findings reveal an average total cost of IDR. 4,127,127 per harvest, which is the total revenue of IDR9,772,500 per harvest, and a total income of IDR5,645,373 per harvest. The calculated R/C value is 2.36, while the B/C value is 1.36. Therefore, it can be said that the copra business in West Tulabolo Village shows that it is feasible to continue, as evidenced by the R/C and B/C ratios exceeding 1.